PENGEMBANGAN BAHASA ANAK USIA DINI 5-6 TAHUN MELALUI MEDIA AUDIO VISUAL ANIMASI DI TAMAN KANAK-KANAK TK KARTINI LEDOKOMBO JEMBER - Nur Fuadiyah, Muthiya; Hisbiyatul Hasanah; Selasi Priatiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve the language competence of children aged 5–6 years by incorporating animated audiovisual media into classroom learning activities at TK Kartini, Ledokombo District, Jember Regency. A Classroom Action Research (CAR) approach, following the Kemmis and McTaggart framework, was implemented through two consecutive cycles involving planning, implementation, observation, and reflective evaluation. The research involved fifteen children from Group B as participants. Data were collected using classroom observations, documentation of learning activities, and field notes, then analyzed descriptively through percentage-based quantitative procedures. The results revealed a marked enhancement in children's language competence after the application of animated audiovisual learning media. Prior to the intervention, most participants were classified within the categories of Not Yet Developing and Beginning to Develop. Following the first and second research cycles, however, the proportion of children attaining the Developing as Expected and Highly Developed categories increased considerably. Improvements were evident across multiple aspects of language competence, including listening skills, comprehension of stories, the ability to answer questions appropriately, vocabulary enrichment, and confidence in expressing thoughts and ideas. These findings suggest that the integration of animated audiovisual media provides an effective pedagogical strategy for supporting language competence development in early childhood education.